A methodological approach applied to elaborate alkali-activated binders for mine paste backfills. (March 2022) - Ouffa, Noureddine; Trauchessec, Romain; Benzaazoua, Mostafa; Lecomte, André; Belem, Tikou
Abstract: In cemented paste backfill (CPB), tailings are commonly bound with Portland cement (GU) blended with ground granulated blast furnace slag (GGBFS) and/or fly ash (FA). Instead of using GU, alkali activation of GGBFS and FA is possible; this alternative has been intensively investigated in the concrete field. However, the development of an alkali-activated binder (AAB) recipe suitable to CPBs is still challenging, especially due to the specificities of the mine tailings. This study presents a methodological approach to formulate suitable AAB for CPB at the laboratory scale. First, potentially reactive mine tailings were substituted with fine siliceous sand to investigate the mechanical properties related to the binders; the new CPB was called simulated cemented paste backfill (S-CPB). Secondly, mixtures and pure pastes were created to investigate reaction kinetics and microstructural properties of such binders by various techniques. This methodological approach allowed the optimization of the binder composition and mechanical properties independently of the mine tailing characteristics. Once satisfactory formulations were elaborated, they were applied to the CPB and were evaluated economically and environmentally in terms of CO2-eq. Results showed that 75GGBFS/25FA_F activated by NaOH within a [0.5 N; 1 N] concentration interval can be used as a binder in CPB instead of the traditional GU/GGBFS blended binder. These findings and methodology are promising and could help to promote new eco-friendly binders in CPBs. However, the cost of NaOH and the CO2-eq footprint are still significant, so further considerations and research are needed to apply AAB in CPB at an industrial scale.